2022
DOI: 10.1111/jfbc.14059
|View full text |Cite
|
Sign up to set email alerts
|

2′‐Fucosyllactose promotes Lactobacillus rhamnosus KLDS 8001 to repair LPS‐induced damage in Caco‐2 cells

Abstract: The aim of this study was to investigate the effect of 2'‐fucosyllactose (2′‐FL) on the repair of monolayer barrier damage in Caco‐2 cells by Lactobacillus rhamnosus KLDS 8001 (KLDS 8001). The results showed that the addition of 2′‐FL not only promoted the adhesion ability of KLDS 8001 to Caco‐2 cells but also improved the anti‐adhesive effect of pathogenic bacteria. Compared with 2′‐FL or KLDS 8001 alone, 2′‐FL+KLDS 8001 significantly reduced lipopolysaccharide (LPS)‐induced malondialdehyde (MDA), lactate deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Intrinsic to the set-up of the study, using 1oral administration of 2 -FL, we cannot distinguish whether the effects on liver or gut are direct, e.g., via 2 -FL itself or metabolites formed from 2 -FL, or more indirect, i.e., mediated via other metabolites that do not directly stem from 2 -FL but are produced by the altered microbiota as a whole. Consequently, the study design does also not allow investigation of the exact molecular mechanisms that mediate gut permeability effects, but this has been studied by others: 2 -FL directly increased expression of tight junction expression proteins, involved in the regulation of gut barrier integrity, in LPS-treated Caco2 cells (49) and directly diminished LPS-induced inflammation in human enterocytes (50) and Caco2 cells (49). Indirect effects of 2 -FL have been demonstrated by using 2 -FL derived bacterial metabolites, which attenuated paracellular permeability of FITC-dextran's in Caco2 monolayers and upregulated the expression of tight junction proteins in a gut-on-a-chip model generated from human gut tissue biopsies (51).…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic to the set-up of the study, using 1oral administration of 2 -FL, we cannot distinguish whether the effects on liver or gut are direct, e.g., via 2 -FL itself or metabolites formed from 2 -FL, or more indirect, i.e., mediated via other metabolites that do not directly stem from 2 -FL but are produced by the altered microbiota as a whole. Consequently, the study design does also not allow investigation of the exact molecular mechanisms that mediate gut permeability effects, but this has been studied by others: 2 -FL directly increased expression of tight junction expression proteins, involved in the regulation of gut barrier integrity, in LPS-treated Caco2 cells (49) and directly diminished LPS-induced inflammation in human enterocytes (50) and Caco2 cells (49). Indirect effects of 2 -FL have been demonstrated by using 2 -FL derived bacterial metabolites, which attenuated paracellular permeability of FITC-dextran's in Caco2 monolayers and upregulated the expression of tight junction proteins in a gut-on-a-chip model generated from human gut tissue biopsies (51).…”
Section: Discussionmentioning
confidence: 99%
“…14 LDH expression is commonly used as an indicator to assess cell damage. 43 Our results indicated that the BH metabolites in the supernatant after 36 hours of fermentation significantly reduced LDH release induced by ETEC, thereby playing a positive role in protecting the membrane integrity of IPEC-J2 cells. Additionally, the production of cytokines is considered a crucial indicator of the response to ETEC infection.…”
Section: Discussionmentioning
confidence: 50%
“…For instance, Lactobacillus species exert well-documented beneficial effects on the intestinal barrier. [141][142][143][144][145][146][147][148][149] The concurrent use of different probiotics can alleviate dextran Sulfate sodium salt-induced colitis by rectifying microbial dysbiosis and compromised barrier function. 150,151 Fecal bacterial transplantation to treat intestinal barrier defects has received TherapeuTic advances in Gastroenterology considerable attention.…”
Section: Clinical Treatmentmentioning
confidence: 99%